POTENSI EKOSISTEM MANGROVE UNTUK MENUNJANG KEBERADAAN EKOWISATA DI KAWASAN TELUK LOMBOK, TAMAN NASIONAL KUTAI, KALIMANTAN TIMUR - , Zahrotun Nisaa Asih Daryono, Dr. Erny Poedjirahajoe, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Kutai National Park is one of national park located in East Kalimantan. This area has a mangrove forest that stretches along the Makassar Strait and its presence increasingly threatened by the destruction of mangrove forests. To maintain the existence of mangrove forests, it is necessary to preserve mangroves by developing ecotourism. The aimed of this study was to determine the diversity of flora and fauna of mangrove and create the tourism loop trail based on the location of flora and fauna. The results showed that mangrove forest in Teluk Lombok has 42 species of mangrove which consists of 17 true mangrove species and 25 species of mangrove associates, 33 species of bird, and 10 species of nekton. The results of the flora assessment showed that Ceriops decandra is included in the category of flora which is âmost interestedâ. While, Clerodendrum sp, Scyphiphora hydrophyllacea, Rhizophora apiculata, Rhizophora mucronata, Rhyzophora stylosa, Bruguiera gymnorrhiza, Bruguiera sexangula, Ceriops tagal, Sonneratia alba, Avicennia marina, Lumnitzera littorea, Lumnitzera racemosa, Excoecaria agallocha, and Acrostichum aureum are included in the category of âinterestedâ flora. The result of the fauna assessment showed that Leptoptilos javanicus, Todirhamphus chloris, Rhipidura javanica, Nectarinia calcostetha, Phaenicophaeus sumatranus, Haliastur indus, Haliaeetus leucogaster, Egretta sacra, Geopelia striata, Cyornis rufigastra, Nectarinia jugularis, Pycnonotus goiavier, dan Orthotomus ruficeps are included in the category of âinterestedâ fauna. For developing ecotourism, two tourism loop trails are made and compared by using Index of Similarity. Index of Similarity values for the type of flora species is 43.64% which indicates that both loop trails have different types of flora, while the Index of Similarity for fauna species is 54.24% which indicates that both of loop trails have almost the same type of fauna. Therefore, the two tourism loop trails can be considered as loop trails which the mangrove flora as the main object and mangrove fauna as the supporting object.